Long-term measurement of sub-3 nm particles and their precursor gases in the boreal forest - J. Sulo; N. Sarnela; J. Kontkanen; L. Ahonen; P. Paasonen; T. Laurila; T. Jokinen; J. Kangasluoma; J. Kangasluoma; H. Junninen; H. Junninen; M. Sipilä; et al. (Atmospheric Chemistry and Physics, 2021)
The knowledge of the dynamics of sub-3 nm particles in the atmosphere is crucial for our understanding of the first steps of atmospheric new particle formation. Therefore, accurate and stable long-term measurements of the smallest atmospheric particles are needed. In this study, we analyzed over 5 years of particle concentrations in size classes 1.1–1.7 and 1.7–2.5 nm obtained with the particle size magnifier (PSM) and 3 years of precursor vapor concentrations measured with the chemical ionization atmospheric pressure interface time-of-flight mass spectrometer (CI-APi-ToF) at the SMEAR II station in Hyytiälä, Finland. The results show that there are significant seasonal differences in median concentrations of sub-3 nm particles, but the two size classes behave partly differently. The 1.1–1.7 nm particle concentrations are highest in summer, while the 1.7–2.5 nm particle concentrations are highest in springtime. The 1.7–2.5 nm particles exhibit a daytime maximum in all seasons, while the 1.1–1.7 nm particles have an additional evening maximum during spring and summer. Aerosol precursor vapors have notable diurnal and seasonal differences as well. Sulfuric acid and highly oxygenated organic molecule (HOM) monomer concentrations have clear daytime maxima, while HOM dimers have their maxima during the night. HOM concentrations for both monomers and dimers are the highest during summer and the lowest during winter following the biogenic activity in the surrounding forest. Sulfuric acid concentrations are the highest during spring and summer, with autumn and winter concentrations being 2 to 3 times lower. A correlation analysis between the sub-3 nm concentrations and aerosol precursor vapor concentrations indicates that both HOMs (particularly their dimers) and sulfuric acid play a significant role in new particle formation in the boreal forest. Our analysis also suggests that there might be seasonal differences in new particle formation pathways that need to be investigated further.